Antagonistic Communicative Function Of Pakistani Trolling Tweets - Zara Obaid & Muhammad Asim Mahmood (corresponding author) (Migration Letters, 2024)
Trolling phenomenon has not been an area of interest until very recently in 2010 (Hardaker, 2017). This saw a surge in trolling researches but mostly from a Euro-centric perspective since the use of social media started very early in those societies. However, trolling language like any other form of language is contextual (Cruz et al., 2018; Fichman & Sanfilippo, 2015, 2016, Phillips, 2021). Hence, it should be investigated as such. Therefore, in order to understand the language of trolling in Pakistan, this study in continuation to previous research (Obaid et al, 2023) explores lexico-grammatical variation of trolling tweets in Pakistan. For this purpose, a corpus of 2,317 trolling tweets is used which is explored through short text multidimensional analysis proposed by Clarke (2019, 2020). The data is run through R software using multiple correspondence analysis. The results reveal that one of the dimensions of Pakistani trolling tweets contrast between antagonistic and conciliatory tweets where the former are more confrontational in their communicative function whereas the latter are non-confrontational. This study adds to the understanding of phenomenon of trolling not only in Pakistan but also corroborates previous notions of trolling.